(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to develop and test the feasibility of an interactive hand puppet learning aid for teaching simple arithmetic operations to Year 2 primary school pupils. The study employed the Research and Development (R&D) method using the ADDIE development model, which comprises the analysis, design, development, implementation, and evaluation stages. The research subjects were 24 Year 2 pupils at SD Negeri 54 Salupikung, whilst the research object was the interactive hand puppet learning medium. Data collection techniques included interviews, questionnaires, and tests, with data analysis conducted both qualitatively and quantitatively. The product developed was an interactive hand puppet resembling the cartoon characters Nussa and Rara, equipped with symbols for simple arithmetic operations. The validity test results indicated that the media fell into the ‘highly valid’ category, with a score of 84.9% from media experts and 94.4% from subject matter experts. The practicality test conducted by the pupils yielded a score of 90.2%, falling into the ‘highly practical’ category. Furthermore, the results of the effectiveness test using an N-Gain of 0.81 indicate that the interactive hand puppet learning medium is effective in improving pupils’ learning outcomes in simple arithmetic operations. Consequently, the learning medium developed is deemed valid, practical, and effective for use in mathematics lessons in Year 2 of primary school.